TEMPERATURE-ACTIVATED ENZYMATIC EXFOLIATION AS A NON-IRRITANT RESURFACING ALTERNATIVE: BIOCHEMICAL RATIONALE AND IN-VIVO SKIN RESPONSE - Женжеруха, Оксана (SWorldJournal, 2026)
The article is devoted to the study of temperature-activated enzymatic peeling as a gentle, non-aggressive alternative to traditional chemical methods of skin renewal. The purpose of the article is to show the biochemical features of peeling and review th